The globaliztion of music in history - Wetzel, Richard D. (Routledge studies on history and globalization., 2012)
This book contextualizes a globalization process that has since ancient times involved the creation, use, and world-wide movement of song, instrumental music, musical drama, music with dance, concert, secular, popular and religious music. Integral to the process have been political, economic, military, and religious forces that motivated or compelled performers to travel, often far beyond the borders of their homelands, to practice their art and craft. That this music was often a traveling companion to non-musical movements—military campaigns, religious missions, political events –does not make the distance it traveled, nor its cultural and social impact, less remarkable.